Shame and eating psychopathology in Portuguese women: Exploring the roles of self-judgment and fears of receiving compassion. (1st March 2017) - Oliveira, Vanessa Raquel; Ferreira, Cláudia; Mendes, Ana Laura; Marta-Simões, Joana
Abstract: Shame has been for long associated with the development and maintenance of body image and eating-related difficulties. However, the mechanisms underlying this association remain unclear. Therefore, the current study sought to examine the mechanisms of self-judgment and fears of receiving compassion from others in the association between external shame and disordered eating, while controlling for body mass index (BMI). Participants in this study were 400 women from the general population, aged between 18 and 55 years old. Correlation analyses revealed significant and positive relationships between external shame, self-judgment, fears of receiving compassion from others and eating psychopathology. A path analysis confirmed that, when controlling for the effect of BMI, external shame has a direct effect on disordered eating severity, and also an indirect effect, mediated by higher levels of self-judgment and increased fears of receiving others' kindness and compassion. Results showed the plausibility of the tested model which explained 36% of the variance of disordered eating. These findings seem to support that women who perceive that others view them negatively tend to be defensive and engage in maladaptive emotion regulation strategies (such as harsh critical attitudes towards the self and being resistant to others' compassion), which may trigger maladaptive eating attitudes and behaviours. The current research appears to be an innovative study in the field of body image and eating-related psychopathology and seems to represent a new avenue for future research and for the development of intervention programs.